Peningkatan Kesadaran Hukum Perlindungan Anak dalam Keluarga pada Forum PUSPA Dinas Sosial Kota Mojokerto - Nurhayati, Ida; Cipta Bidhari, Sandhika; Efriyanto; Azzahra, Kayila; Sawitri, Imelda Nadya; Rachma, Syifa Septia (Universitas Dinamika, 2026)
In Indonesia, child protection is specifically governed by Law Number 35 of 2014 concerning the Amendment to Law Number 23 of 2002 on Child Protection. Mojokerto recorded a total of 49 cases of violence against women and children in 2024. According to data from the Integrated Service Center for Women's and Children's Empowerment (P2TP2A) of Mojokerto City, the majority of the victims were children, specifically 37 individuals ranging in age from toddlers up to 16 years old. This activity was aimed at enhancing the understanding, knowledge, and awareness of family law, with a particular focus on child protection and rights. The methodology involved observation, socialization, and relevant discussions. The session involved 27 participants who are members and board members of the Public Participation Forum for Women's and Children's Welfare (PUSPA), operating under the Mojokerto City Social Service. The outcome demonstrated that 85.2% of the participants understood and applied the Child Protection regulations and laws within their family lives. With this high level of understanding and implementation, there is an opportunity to create an effective intervention model that can help optimize child protection in Indonesia.